O papel da punição disciplinar no controle da tropa da polícia militar do Amazonas - Cordeiro, Euler Carlos de Souza (2008)
The work is to undertake a review of the control system's internal disciplinary Military Police of Amazonas (PMAM) as a way to identify factors that deserve to be modified or improved before the current social situation that is presented to our Public Military Force. For this purpose discussing the elements motivating and purpose of disciplinary punishment to the question 'Why punish?'. Then were the legal aspects of legal and disciplinary reprimand the legislation in force. It was subsequently approached the concept of police activity in Brazil and its peculiarities, moving then to examine the main figures of our state correctional compared with other states of the country. Before closing, we analyze the data Search Field watching the view of commanders and commanded the respect of the disciplinary system now in military force.